Associations Between Vaginal Bacteria and Bacterial Vaginosis Signs and Symptoms: A Comparative Study of Kenyan and American Women - Carter, Kayla A.; Balkus, Jennifer E.; Anzala, Omu; Kimani, Joshua; Hoffman, Noah G.; Fiedler, Tina L.; Mochache, Vernon; Fredricks, David N.; McClelland, Raymond Scott; Srinivasan, Sujatha (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Bacterial colonization and associations with bacterial vaginosis (BV) signs and symptoms (Amsel criteria) may vary between populations. We assessed relationships between vaginal bacteria and Amsel criteria among two populations. Methods: Kenyan participants from the placebo arm of the Preventing Vaginal Infections (PVI) trial and participants from a Seattle-based cross-sectional BV study were included. Amsel criteria were recorded at study visits, and the vaginal microbiota was characterized using 16S rRNA gene sequencing. Logistic regression models, accounting for repeat visits as appropriate, were fit to evaluate associations between bacterial relative abundance and each Amsel criterion. Results: Among 84 PVI participants (496 observations) and 220 Seattle participants, the prevalence of amine odor was 25% and 40%, clue cells 16% and 37%, vaginal discharge 10% and 52%, elevated vaginal pH 69% and 67%, and BV 13% and 44%, respectively. BV-associated bacterium 1 (BVAB1) was positively associated with all Amsel criteria in both populations. Eggerthella type 1, Fannyhessea (Atopobium) vaginae, Gardnerella spp., Sneathia amnii, and Sneathia sanguinegens were positively associated with all Amsel criteria in the Seattle study, and all but discharge in the PVI trial. Conclusions: Core vaginal bacteria are consistently associated with BV signs and symptoms across two distinct populations of women.